Budd-Chiari syndrome in Behcet's disease: A report of two cases - Zhou, Jun (Exp Ther Med, 2019)
Budd-Chiari syndrome (BCS) is a rare but severe venous form of Behcet's disease (BD) that is caused by the obstruction of the venous outflow tract that transports blood from hepatic veins into the inferior vena cava. In countries where BD is prevalent, including the Middle East and Far East, BCS awareness is important. In the present study, two cases of BCS are presented in two male Chinese patients with BD. The clinical characteristics, treatment and outcomes were recorded and compared with previous studies, and the features of BD-BCS were summarized. The clinical characteristics of the two patients documented were similar. Each patient presented with insidious onset, abdominal symptoms and recurrent aphthous ulcers. Accurate diagnosis was delayed as other symptoms of BD were overlooked. Each patient responded well to TNF-α inhibitor treatment in combination with cyclophosphamide (CYC). One patient with good compliance was removed from CYC and corticosteroid therapy. Unfortunately, the other patient with poor compliance faced a poor outcome. It was concluded that multiple vessel lesions in ≥2 sites are common in vasculo-BD and that misdiagnosis may occur if other symptoms of BD are not noticed. BD-BCS is associated with a high mortality rate, but appropriate treatment may result in a favorable outcome.